A visual, journal practice: Journal of Visual Art Practice, twenty years on. (2nd October 2021) - Birkin, Jane; D'Souza, Ed; Manghani, Sunil
ABSTRACT: This editorial introduction marks the 20-year anniversary of Journal of Visual Art Practice . It sets out the vision of the newly established editorial team, who took up the editorship of the journal at the start of 2021, which happened to be the journal's 20th year. The article sets out the editors' commitment to an international and diverse approach, which also recognises the rich history and archive of the journal. At its core, the journal remains steadfastly focused on visual art practice . Thus while cognisant of shifting trends and modalities of academic publishing and research, the editors renew the journal's ethos and practical undertaking in presenting the best in new visual art practice research.